Application of Scaffolding Techniques by Teachers in Narrative Writing Instruction for Third-Grade Students with Learning Difficulties - Syaiful Rohman (Educazione: Journal of Education and Learning, 2025)
Students with learning difficulties frequently encounter significant obstacles in producing narrative texts, particularly at the elementary level where foundational literacy skills are established. This qualitative case study examined how classroom and special education teachers applied scaffolding techniques during narrative writing instruction for three third-grade students with learning difficulties at an inclusive public elementary school in Blitar City, East Java, Indonesia. Data were collected through classroom observations across fourteen instructional sessions, semi-structured interviews with two participating teachers, and documentary analysis of student writing samples and instructional records. Thematic analysis following Miles, Huberman, and Saldaña (2014) revealed four principal scaffolding patterns in teachers' practice, namely verbal modeling through think-aloud strategies, graphic organizer-based structural scaffolding, graduated writing prompts aligned with individual zones of proximal development, and peer-mediated collaborative scaffolding. Teachers demonstrated adaptive calibration of support levels in response to observed student progress, although systematic documentation of scaffolding procedures remained limited. The findings indicated that multimodal and adaptively delivered scaffolding substantially enhanced the writing engagement and narrative output quality of students with learning difficulties. The study contributes to the emerging body of inclusive literacy research in Indonesian elementary education and offers practical implications for the design of differentiated writing instruction within inclusive classroom settings.